Molecular analysis of multidrug-resistant E. coli in pediatric UTIs: findings from a Nigerian Hospital - Eunice Damilola Wilkie; Chidinma Vivian Ezeani; Deborah Oluwasola Olasehinde; Omolanke Temitope Oyedemi; Jude Oluwapelumi Alao; Anthonia Olufunke Oluduro; Oluwapelumi Breakthrough Oyetunde (Journal of Infection in Developing Countries)
Introduction: This study aimed to isolate and characterize antibiotic-resistant Escherichia coli from urine samples of children at the Mother and Child Hospital in Ondo State, Nigeria, assessing antibiogram profiling and resistance genes.